THROMBOPHILIA AND THROMBOEMBOLIC COMPLICATIONS ASSOCIATED WITH USE OF ASSISTIVE REPRODUCTIVE TECHNOLOGIES - S. V. Akinshina; A. D. Makatsariya; V. O. Bitsadze; N. S. Stuleva; T. Ya. Mashkova (IRBIS LLC, 2016)
Thromboembolism represents the most serious, potentially fatal complication of assisted reproductive technologies and in most cases is associated with ovarian hyperstimulation syndrome. This article describes the modern aspects of the pathogenesis of ovarian hyperstimulation syndrome, the pathogenesis of thromboembolic complicationsand importance of genetic and acquired thrombophilia for their development, methods of risk assessment of thrombotic complications before using assisted reproductive technology and recommendations for prevention of thromboembolic complications in women enrolled in an IVF program.